(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2017)
This study included assessing the efficiency of drinking water treatment station in Alhussein Avenue/Alhamza Alkerbi District taking samples collected from December 2015 until February 2016. Measured physical and chemical factors affecting water quality. Water temperature ranging from (13-19) Cº and the highest value registered was in fourth site during the second half of December and during the first and second halves of the month of February. Electrical connectivity values ranged between (950-1620) µs /cm and the highest value in fourth site in the first half of December. PH values recorded were between (7.2-8.1), As the results of the study showed that variation in turbidity values ranged between(3.6-7.2) (NTU). While the remaining chlorine values ranged between (1.7-5) mg/l, and Nitrite values ranging(7-15) µg/l. Reactive phosphate values ranged between (0.01-0.3) µg/l, Total dissolved solids values ranged between (450-807) mg/l and. While total suspended solids values ranged between (0.2-0.8) mg/l and the highest value was in the first site and the second and fourth during the first half of December. The results of the current study pointed to a discrepancy in values of some elements such as iron and zinc iron values ranging between (0.01-0.08) mg/l, and the highest value in second site during the first half of February. While the highest value of zinc was 0.15 mg/l in the first site during the second half of the month of January.